Selection dynamics of HCV genotype 3 resistance-associated substitutions under direct-acting antiviral therapy pressure - Rodrigues, João Paulo Vilela (2023)
The chronic hepatitis C (CHC) treatment is currently based on the use of direct-acting antivirals (DAAs), and patients infected with hepatitis C virus genotype 3 (GT3) have emerged as a more difficult-to-cure population. The NS5A inhibitor daclatasvir (DCV) and sofosbuvir (SOF), an NS5B viral polymerase inhibitor, are among the drugs that compose more effective and safer treatment regimens. The virus genetic variability is related to resistance-associated substitutions (RASs) that adversely impact DAAs effectiveness. The aims of this study were to analyze the association of NS5A and NS5B RASs and other clinical factors with DAAs regimens effectiveness in patients with GT3 CHC infection. This was a prospective cohort study performed in a Brazilian university hospital. Individuals older than 18 years with GT3 CHC treated with SOF + DCV ± ribavirin (RBV) or SOF + peginterferon (PEG) + RBV were included. Blood samples were collected at baseline and post-treatment. A total of 121 patients were included. Sustained virological response rates were 87.6% for the SOF + DCV ± RBV group and 80.0% for the SOF + PEG + RBV arm. Cirrhosis, prior treatment with interferon/PEG + RBV, and baseline NS5A RAS were associated with higher risk of treatment failure. The NS5A analysis suggested that A30K, Y93H, and RAS at site 62 were related to failure. Interestingly, a likely compensatory effect was shown between A30K and A62T. Emergence of Y93H was always associated with RAS at position 62. The RASs dynamics comprehension is an important tool to indicate more effective treatment for GT3 patients.